Principled blended learning materials for language acquisition - Brian Tomlinson (UPT Bahasa Universitas Tanjungpura, 2023)
(Invited Expert Article) This paper focuses on how the development of principled blended learning materials can facilitate the acquisition of an L2. By materials development I mean the design, production, and utilisation of anything intended to facilitate language acquisition. This could be a story, a listening activity, a debate, a photo, a video, a board game, a communication task, a blog, a discovery task, an advertisement, an e-mail or even a sequence of questions. By principled I mean informed by what we know from research and observation about what best facilitates language acquisition. By blended learning I mean learning which makes use of both face to face and a distance modes to facilitate language acquisition. And by the acquisition of an L2 I mean the gradual development of the ability to communicate effectively in a second or foreign language. To help learners achieve language acquisition I am advocating the principled design and use of blended learning materials. I am also specifying what I think are the four most important principles of language acquisition and for each one deriving and exemplifying principles and procedures of materials development.